Frontline demonstrations in Chhindwara district of Madhya Pradesh : An impact analysis: FRONTLINE DEMONSTRATIONS IN CHHINDWARA DISTRICT (MP) : AN IMPACT ANALYSIS - M PADMAIAH; G D S KUMAR; C SARADA; R K REDDY (Journal of Oilseeds Research, 2014)
Madhya Pradesh is one of the potential States for castor cultivation with highest productivity after Gujarat. Several technologies and crop management options have been developed by Directorate of Oilseeds Research (DOR) and All India Coordinated Research Project (AICRP) on castor centres, that can significantly increase the yield, but adoption of these technologies by farmers has been far less than anticipated. Realizing the importance of extending these technologies for improving the yields at farmers’ level, frontline demonstrations (FLDs) were conducted to show the productivity potential and profitability of improved production and protection technologies by AICRP Castor Chhindwara centre, Madhya Pradesh. The present study assessed the impact of these FLDs in enhancing the yield of castor and the socio-economic factors contributing to the adoption of improved technology by farmers. The results indicated that the mean seed yield and the additional net returns were higher in FLD farmers plots compared to non-FLD farmers. Adoption of farmer was highly correlated with socio-economic characteristics such as knowledge level, farm size and training programmes attended. The major contributing factors for adoption of improved practices were knowledge level and exposure to demonstrations.